2022
DOI: 10.3389/fpsyt.2022.762719
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Depressive Symptoms During the Perinatal Period: A Longitudinal Population-Based Study in China

Abstract: Most women in the perinatal period face sleep issues, which can affect their mental health. Only a few studies have focused on sleep trajectories and depressive symptoms of women during the perinatal period in China. This study aims to explore the development trajectory of sleep quality by classifying pregnant women according to the changes in their sleep quality during pregnancy and postpartum and investigate the correlation between different sleep quality trajectory groups and depressive symptoms. The Pittsb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Specifically, it is the presence of insomnia or poor sleep quality in the postpartum, rather than in late pregnancy, that uniquely predicts PPD and anxiety. These findings corroborate other studies that have evaluated women with a history of depression (28,50), convenience samples (4,46,48,70), and those without a history (31,44,71). Notably, the results of this longitudinal study demonstrate that, when statistically pitting prenatal insomnia and sleep quality versus postpartum insomnia and quality in the same model, the postpartum variables were found to be relatively more important in uniquely contributing to postpartum mood.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, it is the presence of insomnia or poor sleep quality in the postpartum, rather than in late pregnancy, that uniquely predicts PPD and anxiety. These findings corroborate other studies that have evaluated women with a history of depression (28,50), convenience samples (4,46,48,70), and those without a history (31,44,71). Notably, the results of this longitudinal study demonstrate that, when statistically pitting prenatal insomnia and sleep quality versus postpartum insomnia and quality in the same model, the postpartum variables were found to be relatively more important in uniquely contributing to postpartum mood.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the research has focused on sleep either during the prenatal period (29,44,45) or in the postpartum period (27,28,31,46,47). Only a few have assessed sleep during pregnancy and into the postpartum and how it is linked with postpartum mood (28,44,45,48,49). Results from those studies indicate that only postpartum insomnia or poor sleep quality increases the risk of postpartum mood when models adjust for prenatal depression (28,45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated that depressive symptom profiles during pregnancy and the postpartum period seem to be heterogeneous regarding the characteristics and chronicity of symptoms. 4 15 …”
Section: Introductionmentioning
confidence: 99%
“… 13 , 15 A longitudinal study of perinatal women in China ( n = 412) reported that the onset and chronicity of depressive symptoms postpartum was associated with poor sleep trajectories prenatally. 12 …”
Section: Introductionmentioning
confidence: 99%